KOORDINASI MENGATASI KEMACETAN LALULINTAS DI KOTA PEKANBARU - Hara Eka Triguna; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The phenomenon of this research is coordinated to address traffic congestion in the city of Pekanbaru already works quite well although implementation is not maximized. One of coordination is not running with maximum meeting activities and meetings division of tasks, whereas in the presence of the meeting can come up with ideas or new ideas in solving traffic congestion problems that occurred in the city of Pekanbaru. The purpose of this study was to determine how the implementation of coordination to address traffic congestion in the city of Pekanbaru and also to determine the factors that influence the implementation of coordination to overcome traffic congestion in the city of Pekanbaru. From hasi study found several factors that affect that. Public awareness, illegal parking, road capacity is not in accordance with the vehicle, the market spilled and the number of members. The most dominant factor in overcoming coordination of traffic congestion in the city of Pekanbaru is a factor of the number of members and public awareness for the coordination process is closely related to public awareness itself. The research was conducted in the city of Pekanbaru his right in the transportation department and Traffic Pekanbaru. Where are the population and sample in this research is the field of road traffic supervision and control of the transportation department and Traffic Operations Pekanbaru. The sampling technique is purposive sampling used in the data collection method of observation, interviews and documentation. After the data were analyzed by using qualitative descriptive analysis. After a study found that coordination to address traffic congestion in the city of Pekanbaru has not been maximized, it can be seen from theory to Henry Fayol were reviewed based on four indicators, namely, communication, cooperation, division of tasks, meetings and meetings.Keywords: traffic congestion in the city of Pekanbaru, communication, cooperation, division of tasks, meetings and meetings.